2006
DOI: 10.1097/01.mlg.0000227997.48020.44
|View full text |Cite
|
Sign up to set email alerts
|

Sphenopalatine Endoscopic Ganglion Block: A Revision of a Traditional Technique for Cluster Headache

Abstract: The diagnosis of chronic cluster headache (CH), the most painful form of headache, is based on typical clinical features characterized by strictly unilateral pain with no side shift and ipsilateral oculofacial autonomic phenomena. The attacks occur several times a day for periods of 1 to 2 months in the episodic form of the disease or less frequently on a daily basis in the chronic form. The pathogenesis of CH involves the activation of parasympathetic nerve structures located within the sphenopalatine ganglio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 12 publications
0
79
1
Order By: Relevance
“…In a study by Ansari et al [53], 95% of patients with facial pain at the beginning of the study reported significant improvement after the study. The facial pain effect size observed in our study (d = 0.96) was much higher than that estimated from Young et al's data (d = 0.51), likely due to the application of multimodal frequencies (70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80) Hz and 1 MHz) in the AxioSonic system. Our effect size for quality of life measures using the SNOT-22 questionnaire (d = 0.45) was lower than Young et al's paper [40] (d = 0.9).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In a study by Ansari et al [53], 95% of patients with facial pain at the beginning of the study reported significant improvement after the study. The facial pain effect size observed in our study (d = 0.96) was much higher than that estimated from Young et al's data (d = 0.51), likely due to the application of multimodal frequencies (70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80) Hz and 1 MHz) in the AxioSonic system. Our effect size for quality of life measures using the SNOT-22 questionnaire (d = 0.45) was lower than Young et al's paper [40] (d = 0.9).…”
Section: Discussioncontrasting
confidence: 55%
“…The SPG is involved in tissue inflammation, lacrimation, mucus production and other parasympathetic processes [71][72][73][74]. Low frequency neurostimulation (20 Hz, much lower than ultrasound frequencies) of the SPG or the Vidian nerve leads to vasodilation and associated inflammation [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…Another study with 20 patients reported on good results, which were always temporarily (Felisati et al 2006).…”
Section: Destructive Proceduresmentioning
confidence: 99%
“…Percutaneous radiofrequency ablation of the sphenopalatine ganglion is performed in many centers, but the evidence base is rather poor. The parasympathetic sphenopalatine ganglion is located in the sphenopalatine fossa, close to the maxillary nerve and the internal maxillary artery, and can be targeted via an infrazygomatic approach or via the lateral nasal wall (Felisati et al 2006). In the most recent published series of 15 patients, the mean attack frequency improved from 17 attacks/week to 8 attacks per week at 18 months follow-up ).…”
Section: Destructive Proceduresmentioning
confidence: 99%
“…After alcohol injection into the SPG, 85% of patients (n¼120) had a relevant decrease of pain (30). Other approaches include radiofrequency ablation (31) ganglionectomy (32), and -less invasive -injections of local anaesthetics (33) or corticosteroids (34) into the SPG. As most of these procedures offer only temporary benefit, and most are destructive and non-adjustable, high-frequency stimulation of the SPG has been suggested as an alternative with promising results in a single case report (35) and a case series (36).…”
Section: Introductionmentioning
confidence: 99%